Development and Biopharmaceutical Evaluation of Tablets Based on the Poorly Water-soluble Substance 1-[2-(2-benzoylphenoxy)ethyl]-6-methyluracil - D. V. Demchenko; E. A. Jain (Korsakova); V. Yu. Balabanyan; M. N. Makarova; V. G. Makarov (Разработка и регистрация лекарственных средств)
Introduction. 1-[2-(2-benzoylphenoxy)ethyl]-6-methyluracil is a substance of scientific interest intended for the treatment of HIV-infection. However, its low bioavailability is a major limitation in successful drug delivery by oral route. Therefore, the objective of the present work was to enhance itssolubility by using solid dispersion technique followed by the development of a solid dosage form.Aim. Development of the composition and technology of tablets based on 1- [2-(2-benzoylphenoxy)ethyl]-6-methyluracil with the appropriate technological properties providing the most complete release of the active pharmaceutical ingredient (API) in vitro.Materials and methods. The pharmaceutical substance 1-[2-(2-benzoylphenoxy) ethyl]-6-methyluracil is a crystalline powder with poor solubility. Solid dispersions were prepared using Lactose, Kollidon® 17PF, Kollidon® 30, Kollidon® VA64, Kollidon 90F, and PEG-6000 as a carrier mostly in 1:4 ratio by two methods – co-melting and solvent evaporation. The technological properties of substance, tablet masses and tablet quality were determined according to the methods described in the State Pharmacopoeia of the Russian Federation (14th edition).Results and discussion. Article shows the results of development of the composition and technology of a medicine in the form of tablets based on the substance 1-[2-(2-benzoylphenoxy)ethyl]-6-methyluracil. Solid dispersion technique was used to improve the biopharmaceutical properties of 1-[2-(2-benzoylphenoxy)ethyl]-6-methyluracil.Conclusion. In vitro dissolution studies showed enhanced dissolution rate of the drug-loaded solid dispersion with Kollidon 17PF as a carrier as compared to pure drug.